(untitled) (Вісник: Міжнародні відносини, 2025)
Background. This article reflects the results of the author’s previous research in Part 1, which gives the author grounds to consider it necessary to refer to already published works in order to avoid repetitions. In Part 2, the author continues the fragmented visual-analytical identification of the morphotypological, psycho-behavioral, anthropological-physiognomic, visual-symbolic features of Franco’s personality and visual images in the cultural and social environment-space constructed by his regime. Methods. The article used the following methods: the method of typological differential-sociological, differential-psychological identification of character structures used in visual analytics and cultural and social systemology. Results. Franco’s character as a recursion of a set of his identities (primarily religious and professional - military) acted simultaneously as a reflection of the habitus of the military class of Spain and a determinant of the regime he built, which combined the features of Catholicism and clerical integral nationalism. The features of the dictator’s behavior presented in the photographs and videos, as well as in the descriptions of various authors (Lewis, 2002; Payne, 2011; Preston, 1994), create the necessary empirical basis for a fragmentary diagnosis of his character as an obsessive-compulsive narcissistic psychopathy with a strongly expressed narcissistic deficiency and peripheral signs of an oral-schizoid constitution. Such a multi-base character structure corresponded, on the one hand, to Franco’s Jewish (Marrano) identities, and, on the other hand, to a set of Ibero-Mediterranean ethnocultural identities expressed in the anthropological and physiognomic features of the dictator’s appearance and observed behavior in different periods of his life. Franco’s strategy of life activity reflected the results of the completed ethnocultural assimilation of his ethnic identities by the national-territorial (civil-state) identities of Spain, which received a specific refraction in the choice of Falangist symbols. The unconscious motivational background of her choice was determined by both a number of generalized socio-cultural factors and the psychobiographical features of Franco, oriented toward the image of the Trastamara dynasty as a referential identity, including for the restoration of the monarchy in Spain. Franco the restorer himself perceived himself as a caudillo (leader) with monarchical powers obtained not in line with traditional monarchical legitimacy, but as a result of a new type of crusade (against the communists and liberals), which implied a counter-modernization understanding of the socio-historical mission of Spain in Europe. Early Franco with his bodily-morphological features in characterology corresponds to the oral-schizoid type, which undergoes transformations in the direction of compulsive psychopathy in the course of military expeditionary socialization in Africa, while maintaining a pronounced narcissistic deficit. The latter was determined by both the complex dynamics of the relations of Franco’s ethnic subgroup with Spanish society and its ethnospecific defenses, and by object relations in the family, in which the experience of Franco’s personality being devalued by his father and the idealization of his mother created the prerequisites for the specific suggestibility of the dictator by his wife along the line of his positive mirroring. The misalliance of Franco and his wife in family identities turned into one of the prerequisites for the cronyism and favoritism of the late Francoist regime.